2016
DOI: 10.1016/j.anorl.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Results of transnasal transostial sphenoidotomy in 79 cases of chronic sphenoid sinusitis

Abstract: The transnasal transostial surgical approach is a safe and effective procedure for the treatment of isolated sphenoid sinusitis. However, the recurrence rate due to postoperative closure of the sphenoidotomy observed in our series raises the question of postoperative maintenance of a patent and functional sphenoidotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…With regards the sinuses, microbiota studies are generally more limited in terms of sample size, but typically report recovery of these bacterial taxa in less than 5% healthy individuals [ 7 , 9 ]. Rather, these bacteria are typically associated with infradiaphragmatic sources and have been implicated as potential pathogens in rhinosinusitis following their isolation in symptomatic individuals [ 10 12 ]. The clinical significance of Leuconostoc carriage by PA patients is unclear and, to the authors knowledge, has not been described in the context of this body site.…”
Section: Discussionmentioning
confidence: 99%
“…With regards the sinuses, microbiota studies are generally more limited in terms of sample size, but typically report recovery of these bacterial taxa in less than 5% healthy individuals [ 7 , 9 ]. Rather, these bacteria are typically associated with infradiaphragmatic sources and have been implicated as potential pathogens in rhinosinusitis following their isolation in symptomatic individuals [ 10 12 ]. The clinical significance of Leuconostoc carriage by PA patients is unclear and, to the authors knowledge, has not been described in the context of this body site.…”
Section: Discussionmentioning
confidence: 99%
“…In ISSOs, the most common diagnosis is inflammation, including rhinosinusitis (bacterial infection), mucocele, and fungal disease. In previous research, the frequency of inflammation was reported as 38–65% 1 , 2 , 8 , 9 . In this study, the total percentage of cases with inflammation, mucocele, and fungal disease was 81%.…”
Section: Discussionmentioning
confidence: 94%
“…Likewise, there was no growth of bacteria in the case of sphenoid sinusitis complicated with sixth nerve palsy [ 12 ]. Massoubre et al [ 13 ] analysed the bacterial flora of 79 patients with isolated chronic sphenoid sinusitis operated on via transnasal approach. Nonspecific inflammation without growth of pathological flora was found in 47 (59.5%) patients.…”
Section: Discussionmentioning
confidence: 99%